Contralateral Breast Primary in Breast Cancer Survivors-An Experience from a Tertiary Care Centre in Thiruvananthapuram, Kerala, India - Manu Paul; Athul K Vasudev; Rexeena V Bhargavan; Kurian Cherian; Paul Augustine (Journal of Clinical and Diagnostic Research, 2021)
Introduction: Improved life expectancy after breast cancer treatment has led to increased incidence of contralateral breast cancers. There are no well established guidelines for the management of these cancers. There is a paucity of Indian data regarding contralateral breast cancers. Aim: To describe the clinicopathological profile and prognostic outlook of patients with contralateral breast cancers. Materials and Methods: This was a retrospective cross-sectional study in which all patients who underwent surgery for non metastatic breast cancer between January 2006-December 2010 at Regional Cancer Centre, Thiruvananthapuram, Kerala, India, were identified. The follow-up data of these patients (6240 patients) were retrieved from medical records division in January 2020. The medical records of all these patients who developed contralateral breast cancer were analysed. Results: A total of 98 patients (1.57%) developed contralateral breast cancer. Most of the second breast cancers were presented at a lower stage than index cancer. Twenty five patients (25.51%) contralateral breast cancers were detected after five years. A total of 58 patients (59.18%) had interval cancer. Among them, 32 (55.17%) were detected by the treating doctor and 26 patients (44.83%) were symptomatic. The median duration of follow-up was 98 months (range 24-150 months). The five year Overall Survival (OS) was 80.5% and five year Disease Free Survival (DFS) was 62.8%. The patients who developed contralateral breast cancer within three years had lower five year OS when compared to those who developed after three years (75.5% vs 86.7% p=0.85). Five year OS was 74.8%, 81% and 85% for patient reported interval cancer, physician detected interval cancers and mammogram detected cancers respectively (p=0.9). Conclusion: Most contralateral breast cancers presented in a lower stage than index cancer. Contralateral breast cancer has got a reasonably good five year OS. There is no significant OS difference between mammogram detected second cancer and interval cancer. There was a need for more frequent clinical breast examination even after five years to detect contralateral primary in an early stage. Cost effectiveness of frequent followup mammogram examinations compared to clinical examination should be evaluated in future prospective studies.